2020
DOI: 10.3390/ijerph17186563
|View full text |Cite
|
Sign up to set email alerts
|

Association between Trace Elements and Body Composition Parameters in Endurance Runners

Abstract: The aim of this study was to determine the possible correlations between essential and toxic trace elements of plasma with several anthropometric and body composition parameters and performance in endurance runners. Sixty-five high-level middle and long-distance runners (21  ±  3 years; 1.77 ± 0.05 m; 64.97 ± 7.36 kg; VO2 max. 67.55 ± 4.11 mL/min/kg) participated in the present study. Abdominal, subscapular, iliac crest, triceps, front thigh and medial calf skinfold thicknesses and an incremental test until ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Interestingly, a recent study found naturally occurring ( i.e. , without supplementation) plasma Li levels to be positively correlated with endurance exercise performance in sixty-five high-level middle and long-distance runners [ 81 ], which appears to support our previous findings in the rodent model. Whether this is due to differences in fibre type composition should be investigated in future studies.…”
Section: Low-dose LI and Musculoskeletal Healthsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, a recent study found naturally occurring ( i.e. , without supplementation) plasma Li levels to be positively correlated with endurance exercise performance in sixty-five high-level middle and long-distance runners [ 81 ], which appears to support our previous findings in the rodent model. Whether this is due to differences in fibre type composition should be investigated in future studies.…”
Section: Low-dose LI and Musculoskeletal Healthsupporting
confidence: 85%
“…This pancreatic protective effect was also observed in STZ mice treated with either LiCl or Li carbonate for 28 days (10 and 8.9 mg/kg/day, respectively), where Li treatment attenuated hyperglycemia, weight loss and polydipsia [ 125 ]. Finally, Jung et al also found that low-dose Li treatment improved insulin-mediated glucose removal in the STZ-induced mouse model of T1D [ 81 , 99 ].…”
Section: Low-dose LI and Obesity And Diabetesmentioning
confidence: 99%
“…According to Barrientos et al, different skinfolds, fat mass, muscle mass, and bone mass correlated positively and negatively with trace elements such as copper. In addition, in a series of athletes, Cu had a negative correlation with the subscapular skinfold, fat mass, muscle mass, and bone mass [62]. Interestingly, 46% (6/13 cases) and 23% (2/13 cases) of the patients with hypercupremia had weight-for-age and height-for-age < 2SDS, respectively.…”
Section: Phenotypical Characteristicsmentioning
confidence: 94%
“…The Collegiate and Professional Sports Dietitians Association (CPSDA) was chartered in 2010 to provide continuing education for and advancement of sports RDs. Since the National Collegiate Athletic Association’s (NCAA) deregulation of feeding in 2014, the number of sports RDs in the collegiate setting has grown exponentially to meet the new demand [ 2 ]. Over the past decade, studies have been conducted to assess nutrition needs and problems of collegiate athletes.…”
Section: Introductionmentioning
confidence: 99%